Relation breastfeeding with the atypical swallowing the pediatric dentistry clinic - Vargas García, Miguel; Eusse Solano, Paola; Alvarado Meza, Jimy (Revista de Investigación en Logopedia, 2021)
From the speech language pathologist, breastfeeding have a decisive role in the structural and functional conformation of the stomatognathic system; being the first function that provides paratypical growth information. Some authors mention that the mandibular balancing movements, typical of breastfeeding, generate excitation on the temporomandibular joint, providing the structure with paratypic stimuli of longitudinal growth, generating transverse growth actions of the skull and face. This study with quantitative paradigm, not experimental, focused on the relationship of breastfeeding with the bad habit of atypical swallowing for the Speech, Language and Hearing Sciences. The Myofunctional Evaluation protocol will be used as a collection instrument, in its skull-facial and functional evaluation sections. The results when analyzing the odds ratio of the logistic regression test, it is evident that there is a protective factor for exclusive breastfeeding, where children who receive artificial breastfeeding are 4.8 times more likely to have atypical swallowing compared to who receive exclusive breastfeeding, and 1.6 in the mixed breastfeeding group, compared with those of exclusive breastfeeding. The preventive aspects of exclusive breastfeeding, denote great importance as an approach to dysfunctional and parafunctional processes, based on a regulation of physiological actions linked in principle to initial feeding, which, to be carried out, needs anatomical structures in optimal state, effective functional actions (sensitive and motor) and adequate guidance from the context.